PRESENTASI DIRI SELEBGRAM PEKANBARU MELALUI MEDIA SOSIAL INSTAGRAM - Laras Pratiwi; Nurjanah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The problem raised in this study is to analyze the phenomenon of self-presentation carried out by celebrities in Pekanbaru through Instagram social media. The main problem in this research is how to present oneself on Instagram social media. m Qualitative research method with a phenomenological approach. Data collection techniques through observation, interviews, and documentation. The theory used in this study is the theory of Dramaturgy by Erving Goffman. In presenting oneself, it is necessary to have a stage as a place that can be divided into two, namely the front stage and the back stage. The research results obtained by self-presentation on Instagram social media have the goal they want, namely what they want to get after presenting themselves is to get the attention of their followers, want to be recognized on Instagram social media, and want to make mementos that can be stored in story archives. on Instagram and want to get engagement. In contrast to the back stage appearance that the celebrity got, they did not think about the target market.